1997
DOI: 10.1111/j.1365-2168.1997.02785.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver resection in the elderly

Abstract: Major hepatic resection can be performed in patients over 65 years old with acceptable morbidity and mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 16 publications
1
44
0
1
Order By: Relevance
“…[8][9][10][11] Despite these advances, the outcome of emergency surgery is less than satisfactory. We found that postoperative complications and mortality in patients aged 80 years and older undergoing emergency surgery were 2.5 times higher than in those aged 65-79 years.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Despite these advances, the outcome of emergency surgery is less than satisfactory. We found that postoperative complications and mortality in patients aged 80 years and older undergoing emergency surgery were 2.5 times higher than in those aged 65-79 years.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 15.7% of the patients with poor ASA score presented with diversion related fistulas, the most frequent complications in this series and those with the most significant impact on hospital stay (29–35 additional days). This was not unexpected as the relevance of the subjective assessment by experienced anesthesiologists in the determination of perioperative risks has been repeatedly confirmed in various types of major surgical procedures such as thoracic surgery [3]and major gastrointestinal surgery [4, 5, 6]. We suggest that cystectomy patients with ASA scores of three or above should be subjected to further preoperative evaluation focusing on parameters that could be improved or corrected.…”
Section: Discussionmentioning
confidence: 99%
“…safe procedure even in older patients because of improved surgical techniques, better perioperative assessment, and advances in anesthesia and medical care. 14,16,17 Human organ function usually deteriorates with age, and older patients have a high incidence of comorbid illness. In addition, HCC is frequently associated with cirrhosis, which is itself a cause of high mortality and morbidity rates after hepatectomy.…”
Section: Commentsmentioning
confidence: 99%
“…We believe that this allows for more reasonable and meaningful comparisons with other previous studies. 4,5,13,14 Other modalities of HCC management, such as percutaneous ethanol injection therapy, microwave coagulation therapy, or percutaneous radiofrequency ablation, can be acceptable alternatives to hepatic resection in older people, but the best treatment for older patients remains controversial. Generally, older patients received significant fewer surgical resections than younger patients.…”
Section: Commentsmentioning
confidence: 99%